Effects of Abuse of Anabolic Androgenic Steroids on Iraqi Athletes - M. Taher, Al-Muhannad; S. Al-Sabbagh, May; K. Al-Khashali, Dawser (Iraqi Journal of Pharmaceutical Sciences, 2017)
Anabolic androgenic steroids (AAS) are man-made derivatives of the male sex hormone testosterone, originally designed for therapeutic uses to provide higher anabolic potency with lower androgenic effects. Increasing numbers of young athletes are using these agents illicitly to enhance physical fitness, appearance, and performance despite their numerous side effects and worldwide banning. Today, their use remains one of the main health problems in sports because of their availability and low price. The present study focuses on investigating the adverse effects of anabolic androgenic steroid abuse on sex hormones, liver and renal function tests, fasting glucose levels and lipid metabolism in Iraqi male recreational bodybuilders. We have recruited fifteen male bodybuilders (age 19-32 years) and an equal number of healthy non-obese, non-AAS-using sedentary controls. Serum hormones (luteinizing hormone (LH), follicle stimulating hormone (FSH), total testosterone, and prolactin), liver function indices (serum alanine aminotransferase (ALT), aspartate aminotransferase(AST), alkaline phosphatase(ALP), total and direct bilirubin), renal function parameters (serum creatinine and urea), lipid profile and serum glucose levels were measured. Abuse of AAS was associated with significant decreases (p< 0.005) in serum levels of LH (66.9%), FSH (49.8 %) and testosterone (63.7%) together with significant increases (p< 0.05) in prolactin concentrations (49.8%) in AAS-using bodybuilders compared to sedentary controls. Anabolic androgenic steroids-using athletes had significantly higher (p< 0.05) circulating levels of total bilirubin (116.3%), direct bilirubin (127.6%), aspartate (1752.9%) and alanine (263.1 %) transaminases than those of sedentary control subjects. Serum alkaline phosphatase levels were not significantly different (p> 0.05) between the two groups. Concerning renal function, AAS-using athletes had significantly higher serum concentrations of creatinine (28.6%) and urea (21.3%) than sedentary controls. Meanwhile, AAS abuse was accompanied by atherogenic lipid profile. Anabolic androgenic steroids -using athletes had significantly higher (p< 0.05) serum levels of triglycerides (TG) (45.6%), low density lipoprotein-cholesterol (LDL-C) (26.0%) and very low density lipoprotein-cholesterol(VLDL-C) (45.6%) together with significantly lower serum concentrations of high density lipoprotein-cholesterol (HDL-C) (31.3%) than sedentary controls. Serum total cholesterol (TC) and fasting glucose concentrations were not significantly different (p> 0.05) between the two groups. The results presented in the study confirm that abuse of AAS induces unfavorable body functions and undesirable side effects. Therefore, efforts should be sought against use of these compounds outside the therapeutic frame.Key words: anabolic steroids, athletes, bodybuilding, exercise.